Marinifilum caeruleilacunae sp. nov., isolated from Yongle Blue Hole in the South China Sea. Issue 5 (4th May 2022) - Dai, Wei; Sun, Wen; Fu, Tianyu; Jia, Chao; Cui, Hongchang; Han, Yanqiong; Shi, Xiaochong; Zhang, Xiao-Hua
Abstract : A Gram-stain-negative, non-motile, facultatively anaerobic and non-flagellated marine bacterium, designated JC070 T was isolated from the Yongle Blue Hole in the South China Sea. The temperature, pH and NaCl ranges for growth of strain JC070 T were 4–37 °C (optimum, 16 °C), pH 6.0–9.0 (optimum, pH 7.0) and 1.0 –6.0% (w/v; optimum, 3.0%). The predominant isoprenoid quinone of strain JC070 T was identified as menaquinone-7. The dominant fatty acids (>10%) were iso-C15:0 (59.6%) and iso-C17:0 3-OH (17.2%). The major polar lipids were aminophospholipid, aminolipid, two unknown phospholipids and two unidentified lipids. The genomic DNA G+C content was determined to be 37.0 mol%. Based on the results of polyphasic analysis, a new species, named Marinifilum caeruleilacunae sp. nov., within the genus Marinifilum was proposed. The type strain is JC070 T (= JCM 39045 T =MCCC 1K03774 T ).